Brain natriuretic peptide in differentiating cardiogenic and non- cardiogenic dyspnoea in patients with renal dysfunction: a single centre study - Renganathan, Sruthi Meenaxshi Subbiah; Rai, Madhukar; P., Tiwari J.; Singh, Tej Bali (International Journal of Research in Medical Sciences, 2021)
Background: Both BNP (Brain Natriuretic Peptide) and renal function are prognostic indicators of survival in patients with congestive heart failure. However, relationship between BNP, renal function and heart failure as an emergency diagnosis are unknown. The usefulness of BNP as a diagnostic tool in patients with renal dysfunction is thus explored in this study. Methods: The present study was prospectively designed diagnostic test evaluation study conducted in Banaras Hindu University, Varanasi. Out of 166 participants with renal dysfunction defined as creatinine >1.5mg/dl who presented with acute dyspnoea, clinical history, BNP, 2D Echo and baseline estimated glomerular filtration rate were assessed. Patients with severe anaemia, eGFR less than 15 ml/min/1.73 m2 and those on dialysis therapy were excluded from the study. The final diagnosis was adjudicated by cardiologist who was blinded to BNP values. Results: The final diagnosis of CHF was in 104 (62.7%). The correlation between BNP and eGFR values were r=-0.49 for those with CHF (p<0.001) and r=-0.279 (p<0.028) for those without CHF. Median BNP in patients with renal dysfunction with CHF was 1206 pg/ml and without CHF was 186 pg/ml. The area under the receiver operating characteristic curve and optimal cutpoints for EGFR categories 59-30 ml /min/1.73 m2 and EGFR less than 30 ml/min/1.73m2 were 0.992 and 491.5 pg/ml (sensitivity 97% and specificity 95%) and 1.000 and 512pg/ml (sensitivity 100% and specificity 95.5%) respectively. Conclusions: Renal function weakly correlates with BNP in patients without CHF (congestive heart failure). BNP is an important bed side tool for distinguishing cardiogenic and non-cardiogenic dyspnoea in patients with renal dysfunction requiring higher diagnostic cut points. Thus the present study emphasises BNP is the strong and independent predictor of CHF even after taking renal function into considerations.